2013
DOI: 10.1097/jtn.0000000000000011
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Behaviors of Infants and Young Children

Abstract: Accidental suffocation and strangulation in bed is a leading cause of preventable infant death. Bed sharing, teen motherhood, and Hispanic ethnicity have been associated with infant sleep suffocation death. Fifty-five Hispanic teen mothers were surveyed regarding acculturation/demographic characteristics and their infants' sleep behaviors. Most participants had 2 foreign-born parents from Latin America. Participants with 2 US-born parents were less likely to bed share than their less-acculturated peers. Many p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In SC, barriers to care include Latinas’ limited access to health insurance and other resources such as health information, putting them at risk for poorer birth outcomes (Torres, Smithwick, Luchok, & Rodman-Rice, 2012). Young Latino parents and caregivers are more likely to employ high risk infant sleeping practices, including co-sleeping and prone positioning (Duzinski et al, 2013). Given the median age of Latinos in SC is 26 (Demographic Profile of Latinos in South Carolina, 2014), there was a clear need for a culturally and linguistically targeted and tailored Tummy Time educational intervention for Latinas in childbearing age.…”
Section: Introductionmentioning
confidence: 99%
“…In SC, barriers to care include Latinas’ limited access to health insurance and other resources such as health information, putting them at risk for poorer birth outcomes (Torres, Smithwick, Luchok, & Rodman-Rice, 2012). Young Latino parents and caregivers are more likely to employ high risk infant sleeping practices, including co-sleeping and prone positioning (Duzinski et al, 2013). Given the median age of Latinos in SC is 26 (Demographic Profile of Latinos in South Carolina, 2014), there was a clear need for a culturally and linguistically targeted and tailored Tummy Time educational intervention for Latinas in childbearing age.…”
Section: Introductionmentioning
confidence: 99%
“…Parents prefer bed sharing for a variety of cultural and personal reasons, such as breastfeeding and ease of attachment (31,32). However, it has been found that bed-sharing increases the risk of SIDS by 2.8 times owing to overheating, rebreathing of air, obstruction of the airway, covering the infant's head, and exposure to cigarette smoke (1,31).…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been found that bed-sharing increases the risk of SIDS by 2.8 times owing to overheating, rebreathing of air, obstruction of the airway, covering the infant's head, and exposure to cigarette smoke (1,31). Certain studies describe that bed-sharing is a cultural practice, and practices such as soft bed use and laying the infant in the prone position are correlated with bed-sharing (32,33). Room sharing without bed-sharing has been reported to be safer and to reduce the risk of SIDS by 50% (1,9).…”
Section: Resultsmentioning
confidence: 99%